Design of compliant mechanisms: An explicit topology optimization method using end-constrained spline curves with variable width. (May 2022) - Zhu, Benliang; Wang, Rixin; Liang, Junwen; Lai, Jianhao; Zhang, Hongchuan; Li, Hai; Li, Hao; Nishiwaki, Shinji; Zhang, Xianmin
Abstract: In this study, an approach using moving end-constrained spline (ECS) curves with variable widths is presented for the explicit topology optimization of compliant mechanisms. The proposed approach uses a series of spline curves to represent the topology of the compliant mechanism. Instead of using a fixed width, we let the width of such spline curves vary along the curve. The optimized design is obtained by optimizing the width of the spline curves and the position of the control points. To avoid infeasible solutions in the design process, the end points of several specific spline curves are constrained according to the design region. The validity of the proposed method is demonstrated using different types of splines, such as the Bézier curve and B-spline curve, for the design of a force inverter, a compliant gripper and a compliant orthogonal displacement amplification mechanism. Highlights: An approach using moving wide-Bezier curves for explicit topology optimization of compliant mechanisms is presented. An interpolation function is utilized to represent a wide-Bezier curve with variable width. The ends of all utilized wide-Bezier curves are constrained to stabilize the optimization process.